2016
DOI: 10.1016/j.rchipe.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory viral infections in pediatric cancer patients undergoing chemotherapy

Abstract: Objective: To estimate the prevalence of infection by respiratory viruses in pediatric patients with cancer and acute respiratory infection (ARI) and/or fever. Methods: Cross-sectional study, from January 2011 to December 2012. The secretions of nasopharyngeal aspirates were analyzed in children younger than 21 years with acute respiratory infections. Patients were treated at the Grupo em Defesa da Criança Com Câncer (Grendacc) and University Hospital (HU), Jundiaí, SP. The rapid test was used for detection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
1
2
0
Order By: Relevance
“…Details of pathogens in single and multiple respiratory infections with influenza-positive cases.Similar findings of single and multiple pathogen coinfections with influenza have been reported from Brazil, Turkey, Japan, and China[29][30][31][32][33][34].To the best of our knowledge, this could be the first study undertaken with multiplex RT-PCR kit on 21 respiratory pathogen for detection of influenza A, A/H1N1, influenza B, RV, RSV A-B, PIV 1-4, coronavirus OC43, NL63, 229E, and HKU1, MPV A-B, BV, Mycoplasma pneumoniae, AV, EV, and PeV. Recently, Rutvisuttinunt et al have reported the detection rate of viral pathogens (71.3%) in specimens of ARI cases collected from South East Asian countries including Nepal.…”
supporting
confidence: 83%
“…Details of pathogens in single and multiple respiratory infections with influenza-positive cases.Similar findings of single and multiple pathogen coinfections with influenza have been reported from Brazil, Turkey, Japan, and China[29][30][31][32][33][34].To the best of our knowledge, this could be the first study undertaken with multiplex RT-PCR kit on 21 respiratory pathogen for detection of influenza A, A/H1N1, influenza B, RV, RSV A-B, PIV 1-4, coronavirus OC43, NL63, 229E, and HKU1, MPV A-B, BV, Mycoplasma pneumoniae, AV, EV, and PeV. Recently, Rutvisuttinunt et al have reported the detection rate of viral pathogens (71.3%) in specimens of ARI cases collected from South East Asian countries including Nepal.…”
supporting
confidence: 83%
“…Knowledge on the epidemiology of respiratory viral infection in immunocompromised children is scarce with few systematic studies aimed to determine their clinical impact [6]. RSV, influenza virus, parainfluenza virus, adenovirus and picornaviruses have been the most common aetiological agents detected in this population [6,7,12]. The increasing detection of viruses highlights the relevance of optimizing viral diagnosis in children with FN [1].…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, the most common aetiological agents reported in FN episodes occurring in children with cancer have been bacterial and fungal pathogens. Viral infections, particularly respiratory viruses, have been increasingly recognized as significant aetiological agents of FN in this population [6,7].…”
Section: Introductionmentioning
confidence: 99%